PENGARUH WEBSITE QUALITY TERHADAP USER SATISFACTION YANG DIMEDIASI OLEH SERVICE QUALITY PADA BLIBLI - Khansa Salsabila Syams; Arif Kuswanto (FEB Universitas Sam Ratulangi Manado, 2023)
After the subside of the Covid-19 case which has attacked the whole world including Indonesia for ± 2.5 years, people have started to live a normal life, one of which is in terms of entertainment. Music concerts are entertainment that has a big contribution in Indonesia. With the development of the times, concert ticket sales have collaborated with various platforms to sell tickets online. Blibli is an e-commerce in Indonesia that often works with concert promoters to sell concert tickets. However, many consumers still criticize the quality of the website owned by Blibli because it is often down. Not only that, the quality of Blibli's services is often discussed by consumers because they have not worked optimally. These two things make many consumers dissatisfied with Blibli's performance. This study aims to analyze the effect of Website Quality on User Satisfaction mediated by Service Quality on Blibli. This type of study is quantitative research with descriptive analysis. The number of respondents in this study is 400 with the criteria of having bought concert tickets in Blibli. The sampling technique used is non-probability sampling and a Likert scale. The data analysis used is PLS (Partial Least Square) with SmartPLS 3 software. The results state that Website Quality (X) has a positive and significant influence on User Satisfaction (Y). Website Quality (X) has a positive and significant influence on Service Quality (Z). Service Quality (Z) has a positive and significant influence on User Satisfaction (Y). Website Quality (X) has a positive and significant influence on User Satisfaction (Y) through Service Quality (Z).